2020
DOI: 10.3389/fmicb.2020.01025
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Gut Bacterial Diversity and Captive Husbandry to Optimize Vulture Conservation

Abstract: Endangered species recovery plans often include captive breeding and reintroduction, but success remains rare. Critical for effective recovery is an assessment of captivityinduced changes in adaptive traits of reintroduction candidates. The gut microbiota is one such trait and is particularly important for scavengers exposed to carcass microbiomes. We investigated husbandry-associated differences in the gut microbiota of two Old World vulture species using 16S RNA gene amplicon sequencing. Increased abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Only the middle layer of the fecal ball was collected from these different individuals. Freshly dropped raptor samples were collected by scraping or syringe suction from the surface ( Becker et al, 2020 ). Samples were immediately transferred into 5-ml sterile tubes, placed on dry ice, and stored at −80°C until further processing.…”
Section: Methodsmentioning
confidence: 99%
“…Only the middle layer of the fecal ball was collected from these different individuals. Freshly dropped raptor samples were collected by scraping or syringe suction from the surface ( Becker et al, 2020 ). Samples were immediately transferred into 5-ml sterile tubes, placed on dry ice, and stored at −80°C until further processing.…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have investigated the impact of captivity, a severe lifestyle shift, on avian gut microbiota. Reports on nine species of parrots, red-crowned crane (Grus japonensis), and vultures (Gyps fulvus and Neophron percnopterus) demonstrate that captivity can impact gut microbiomes [5][6][7]. Fewer studies have compared wild and captive gut bacteria and fungi across spatially distinct sites that vary by climate and vegetation [8], which are expected to differ in microbial species pools, a potential source for gut microbes.…”
Section: Introductionmentioning
confidence: 99%
“…However, investigations in wild species in general (Moeller et al., 2017, 2020; Pratte et al., 2018; Song et al., 2020; Youngblut et al., 2019), and avian species in particular (Corl et al., 2020; Gillingham et al., 2019; Grond et al., 2018; Kreisinger et al., 2017; Roggenbuck et al., 2014), are just taking off. Studies in a range of species have shown that the microbiome composition of free‐ranging versus captive conspecifics are significantly different (Becker et al., 2020; Cabana et al., 2019; Clayton et al., 2016; Gibson et al., 2019; Kohl et al., 2014; McKenzie et al., 2017; Wienemann et al., 2011), which highlights the importance of continued study of wild animals. Studies of free‐ranging, wild animals offer the opportunity to understand the factors that influence the composition and dynamics of microbiomes when the hosts are exposed to dynamic and varied environments.…”
Section: Introductionmentioning
confidence: 99%